Field collection date and concentrations of indole-3-butyric acid (IBA) effect on the vegetative propagation of London planetree - Masiero, Michel Andersson; Viana, Carla Marins Santos Santana; de Lima, Daniela Macedo; da Silva, Edvan Costa; Feliceti, Maikely Luana; Salla, Vanessa Padilha; Silveira, Guilherme Sudbrack (Scientia Agraria, 2025)
The London planetree (Platanus acerifolia (Ailton) Wild.) is an exotic tree species native to Asia and the Northern Hemisphere, with relevance in urban landscaping and timber potential. This study evaluated the effects of different collection seasons and the use of indole-3-butyric acid (IBA) at various concentrations on the rooting of semi-woody cuttings of P. acerifolia. Cuttings (10 cm) were collected in autumn, winter, spring, and summer, treated with IBA (0, 3000, and 6000 mg L⁻¹), and maintained in vermiculite for 90 days under shaded nursery conditions. The hypothesis was that collection season would affect rooting and that the auxin could stimulate adventitious root formation. Results showed that collection season significantly influenced all evaluated parameters, while the use of IBA did not show a significant effect on rhizogenesis. Summer 2015–2016 was the most favorable season, with 60.8% of cuttings rooted and the highest number of shoots, due to accelerated vegetative growth and lower tissue lignification. Winter 2015 showed higher mortality (79.2%) and lower rooting. Therefore, the use of cuttings collected in summer is recommended to maximize vegetative propagation of P. acerifolia, ensuring higher rates of root and shoot formation, which are essential for successful field establishment.